Penentuan Sistem Pemuliabiakan dalam Populasi Kambing Saburai untuk Meningkatkan Kinerja Pertumbuhannya - Sulastri Sulastri; Muhammad Dima Iqbal Hamdani; Kusuma Adhianto (Jurnal Riset Agribisnis dan Peternakan, 2016)
The research was conducted with a record of the growth performance of Saburai goats from 2013 to 2015 in the Saburai goat seed source area, Sumberejo District, Tanggamus Regency, Lampung Province. The research objective was to determine the appropriate breeding system to improve the growth performance of the offspring. This goal is achieved through heritability (h2) and repeatability (r) of growth performance (weight and body size at birth, weaning, and age one year). The h2 value was estimated using the step-by-step retreat method, the repeatability (r) was estimated using the permission class method. The results showed that the h2 and r values ​​of growth performance at birth, weaning, and age of one year were medium-class respectively. The h2 value at birth (body weight (BW) 0.10, height (TB) 0.11, body length (PB) 0.13, chest circumference (LD) 0.12, hip height (TP) 0.14) ) and the values ​​at birth (BW 0.12, TB 0.16, PB 0.14, LD 0.14, TP 0.16) are the lowest. The h2 value at weaning age (BW 0.16, TB 0.15, PB 0.16, LD 0.17, TP 0.17) and the r-value at weaning age (BW 0.16, TB 0.15, PB 0 , 16, LD 0.17, TP 0.17) were higher at birth. The value of h2 for one year of age (BW 0.18, TB 0.17, PB 0.16, LD 0.18, TP 0.19) and one year age value (BW 0.21, TB 0.22, PB 0, 22, LD 0.21, TP 0.21) the highest. It is provided that individual selection on the growth performance of weaning age and one year of age is an appropriate breeding system to improve the growth performance of Saburai goats.